Penerapan Metode Read Aloud dalam Meningkatkan Literasi Anak Usia Dini - Ayunda Sayyidatul Ifadah; Ika Irayana (UNIB Press, 2023)
Abstract Literacy is a set of skills that include reading, writing and speaking, numeracy skills, and skills in accessing and using information (Kemendikbud, 2017). In the Program for International Student Assessment (PISA) data was obtained that Indonesia ranked second worst out of 65 countries in the world in 2012. Based on the results of research on children's interest in literacy in Gresik district, it is in the high category, namely 64%. By looking at these results, it is necessary to have a variety of methods used by educators so that a literacy culture in children increases (Ifadah, 2022). One of the learning methods that can develop children's literacy is the read-aloud method. Read Aloud is a method of reading books to children. Based on observations, there is one institution that applies the read-aloud method every day during learning activities. The institution is the Dikara Edu Center (DEC). From the results of interviews with the head of the institution, it was found that 75% of the children participating in activities at DEC experienced an increase in their language development. This made researchers want to study more deeply the read-aloud method at DEC institutions in increasing literacy in children. So that later valid results will be obtained from the success of the read-aloud method in developing children's literacy. Data collection techniques in this study used observation, interviews, documentat on, and data analysis techniques. Data analysis on the Miles and Huberman model consisted of 3 steps, namely data reduction, data display, and conclusion drawing/verification. The results of the study obtained the development of children's literacy in January - March, there were 1-2 children who were still at the stage of starting to develop and 6-5 image aging entering the developing stage according to expectations. Seeing the results of this assessment, it can be seen that children using the read-aloud method can improve literacy in children